Requirements and Procedures for Meat Import in Indonesia and the U.S.A. : A Comparative Study - Sri Raharjo (Indonesian Food and Nutrition Progress, 1999)
In order to protect the consumers from zoonosis diseases and to assure the wholesomeness of imported meat from abroad, a decree on requirements for and supervisions of the importation of meat has been issued by the Minister of Agriculture in 1992. The decree, however, has not been adequately socialized to general public until now. Indonesian meat consumers also have to know how the existing decree measure up with similar regulation in other meat importing country such as the United States of America. The recent debate on the possibility of importing beef from India can be used as a test for the Directorate General of Livestock of the Repbulic of Indonesia in enforcing the decree. The Indonesian and the U.S. requirements and procedures for importation of meat have many things in common. There are, however, at least three major point of differences worth to consider. First, the halal certificate is a must for meat imported into Indonesia. Second, drug and chemical residues are strictly enforced by the FSIS for meat imported to the U.S. Third, the Indonesian National Standard of meat (especially beef) is not adequately prepared to accomodate the imported meat quality and safety specifications